MODEL P1-4 AS THE BASIS OF FORECAST ESTIMATES OF RUSSIA ECONOMIC DEVELOPMENT - V. Antipov (Вестник университета)
The article describes the modification of a P1-4 and the results of the inertial forecast of gross domestic product of the Russian economy until 2030. The Russian economy has no traditional production function, so the model uses the fundamental characteristics of the economy, in particular, the dependence of the number of employees of gross domestic product, the ratio of intermediate consumption, etc. provide a complete list of the model equations.